Technique in RNA isolation of digestive tract from Rhynchophorus ferrugineus (Coleoptera: Dryophthoridae) - Norefrina Shafinaz Md Nor,; Adibah A.B.,; Nurul Hidayah A.S.,; Nurul Wahida O., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
Rhynchophorus ferrugineus (Coleoptera: Dryophthoridae) or also known as Red Palm Weevil (RPW) is a common pest which cause serious problem in palms. Deep understanding towards physiology of its feeding system might provide meaningful insight in managing this pest infestation. This short note was aimed to isolate good quality RNA from salivary glands, midgut and hindgut of R. ferrugineus to be used for gene expression study. A total of four weevils were used to extract RNA from salivary gland while one weevil was used for RNA extraction from midgut and hindgut. Several key measures were taken during tissue harvesting and RNA extraction such as RNAse decontamination of working area, tissue storage in liquid nitrogen and RNAlater® upon dissection and slight modification during tissue disruption. Total yield for RNA of salivary glands, midgut and hindgut were 6.9 µg, 46.1 µg and 7.2 µg in 20 µL respectively. Quality of the RNA from all tissues were also good with 260/280 ratio being above 2. In addition, Bioanalyzer analysis also gave high RIN number for all RNA. In conclusion, the techniques utilised for RNA extraction from salivary gland, midgut and hindgut of red palm weevil able to yield good quality and quantity of RNA.